(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
: Because of its rigour, the Italian law bearing the denomination “Regula-tions on medically assisted reproduction” has been strongly debated from the very beginning and gradually dismantled by jurisprudence. In this article, the authors re-mark that the path followed by jurisprudence is characterized by the total absence of care regarding the unborn child’s rights. The authors rather suggest that the ap-proach of jurisprudence should be guided by considerations on the substance of the law at issue, investigating all the issues involved, including those concerning the position of the unborn baby, as stated by the ratio of the same law.